Prepartum Eclampsia in a Tibetan Crossbred Bitch - A case Report - JANA, D; JANA, M; CHAKRABORTY, D (The Indian Journal of Animal Reproduction, 2023)
A primiparous Tibetan crossbred bitch (Tibetan spaniel X Lhasa - Apso) named Julli aged about four years was brought to the Block Veterinary Dispensary with a history of 6 5 days pregnancy and associated complaints of fever, anorexia, restlessness and convulsions. The owner also reported that there were intermittent discharge of clearfluid per-vagina four· daysear lier. The bitch was in eclamptic convulsion and in recumbant state. Twitching of muscles of face, tongue and limbs and stertorous breathing with frothy secretions filling the mouth were noticed. This followed muscular rigidity and occasional tremors. Pupils were dilated. Typical panting with exagerated respiration was predominant. Face seemed to be distorted after few seconds of convulsions. Legs were inverted. Hyperthermia with rectal temperature 104.5°F was recorded. The tongue held protruded on one side and licking movement was absent. Clinical examination r.evealed the enlarged abdomen and engorged mammary gland. Milk appeared in all the teats. Foetal heart sound was not audible. Per abdominal examination revealed no foetal movement. Per vaginal examination revealed closed cervix with soft texture without any straining.